Optical Properties of Polyvinyl Alcohol-Based Polymer Films Containing Methylene Blue and Trichloroacetic Acid for Gamma Radiation Dosimetry Applications - Doyan, Aris; Prayogi, Saiful; Méité, Namory; Sarkingobir, Yusuf; Kouamé, Alfred Niamien; Yaya, Ouattara Leygnima (Lensa: Jurnal Kependidikan Fisika, 2024)
The primary objective of this study is to investigate the optical properties of polyvinyl alcohol (PVA) based polymer films, incorporating methylene blue (MB) dye and trichloroacetic acid (TCA), for their potential application in gamma radiation dosimetry. Specifically, this research aims to explore the effects of gamma radiation on the color change characteristics, optical absorption spectra, activation energy, and optical band gap energy of the PVA-MB-TCA polymer films. Additionally, the study seeks to assess the stability of these polymer films under varying doses of gamma radiation, ranging up to 14 kGy. The PVA-MB-TCA polymer films were prepared using a solvent-casting method. The polymer film samples were then exposed to gamma radiation from a 60Co source, with doses up to 14 kGy. The study observed significant color changes in the polymer films, transitioning from blue at 0 kGy to light blue-near transparent at 14 kGy. Spectrophotometric analysis identified three distinct wavelengths of maximum absorption at 360 nm, 440 nm, and 560 nm. As the radiation dose increased, absorption values decreased at 360 nm and 440 nm, while an opposite trend was noted at 560 nm. Furthermore, the activation energy of the polymer films was found to decrease with increasing radiation doses, indicating a reduction in the energy barriers for internal reactions. Similarly, the optical band gap energy also showed a decreasing trend with higher radiation doses across all types of transitions. These results demonstrate that the PVA-MB-TCA polymer films undergo significant optical and structural changes when exposed to gamma radiation, highlighting their potential utility as reliable high-dose radiation dosimeters. The stability of these films under radiation further supports their applicability in various fields requiring precise radiation dose monitoring, such as medical sterilization, food processing, and environmental safety.